New Advances into Nanostructured Oxides, 2nd Edition - Silvia Mostoni; Roberto Nisticò (Inorganics, 2025)
The interest in inorganic nanostructured oxides is growing extensively, thanks to their remarkable features and their wide range of applications, which include (photo)catalysis [...]